2017
DOI: 10.1016/j.mri.2016.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Advanced diffusion models in head and neck squamous cell carcinoma patients: Goodness of fit, relationships among diffusion parameters and comparison with dynamic contrast-enhanced perfusion

Abstract: Purpose:We assessed advanced fitting models of diffusion weighted imaging (DWI) in head/neck squamous cell carcinoma (HNSCC) patients to determine the best goodness of fit and correlations among diffusion parameters. We compared these results with those of dynamic contrast-enhanced (DCE) perfusion parameters. Conclusion:We identified several correlations between DWI parameters by advanced fitting models and correlations between DWI and DCE parameters. These will help determine HNSCC patients' detailed tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…Our present analyses revealed that the combination of D 2 and D 3 in tri-exponential fitting is an indicator that could be used for the prediction of high tumor growth rates. Using a tri-exponential fitting model for HNSCC, another research group speculated that D 2 fairly or moderately reflects the diffusion of the segment in the extracellular extravascular space (EES), whereas D 3 also reflects the cellular component [7]. Based on our present findings, we also speculate that HNSCCs with a high growth rate will have decreased water diffusivity in the EES caused by the strongly elevated tumor cellular density in its microenvironment.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Our present analyses revealed that the combination of D 2 and D 3 in tri-exponential fitting is an indicator that could be used for the prediction of high tumor growth rates. Using a tri-exponential fitting model for HNSCC, another research group speculated that D 2 fairly or moderately reflects the diffusion of the segment in the extracellular extravascular space (EES), whereas D 3 also reflects the cellular component [7]. Based on our present findings, we also speculate that HNSCCs with a high growth rate will have decreased water diffusivity in the EES caused by the strongly elevated tumor cellular density in its microenvironment.…”
Section: Discussionsupporting
confidence: 66%
“…The biological characteristics of these two groups might be somewhat different, and thus a further subgroup analysis is needed. However, the diffusion parameters of these two subtypes were reported to not differ significantly [7]. We also found that the information of the primary site was not significantly associated with the tumor growth rate in a univariate analysis.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In addition, it is also informative to compare different non-Gaussian diffusion models using the same high-b diffusion data sets. A comprehensive comparison between different non-Gaussian diffusion models has been performed in healthy subjects (23) and cancer patients (24) previously.…”
Section: Introductionmentioning
confidence: 99%